The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1515/forum-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

Chain conditions for graph C*-algebras

Abstract: In this article, we study chain conditions for graph C*-algebras. We show that there are infinitely many mutually non isomorphic Noetherian (and Artinian) purely infinite graph C*-algebras with infinitely many ideals. We prove that if E is a graph, then {C^{*}(E)} is a Noetherian (resp. Artinian) C*-algebra if and only if E satisfies condition (K) and each ascending (resp. descending) sequence of admissible pairs of E stabilizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Noetherian and/or Artinian C*-algebras as well as C*-algebras with Krull dimension are defined and studied in [20,34,35,40,41]. In this article, we define and study C*-algebras with Goldie dimension as a generalization of all of these classes (see Figure 1), and then extend the main results obtained in [41] and present some new results and applications.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Noetherian and/or Artinian C*-algebras as well as C*-algebras with Krull dimension are defined and studied in [20,34,35,40,41]. In this article, we define and study C*-algebras with Goldie dimension as a generalization of all of these classes (see Figure 1), and then extend the main results obtained in [41] and present some new results and applications.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, for a complete-Goldie C*-algebra, Goldie dimension is preserved under Morita equivalence of C*-algebras and passes to ideals and quotients, by Theorem 2.7(i) and Definition 2.22. The first assertion now follow from [40, Lemma 3.3]. The second assertion holds, because in [21, Theorem 2.5], it was shown that if E is a directed graph, then satisfies Condition (K) if and only if the real rank of is zero.…”
Section: Goldie Dimension For C*-algebrasmentioning
confidence: 95%
See 3 more Smart Citations